THE EFFECTIVENESS OF TOURISM VLOG COMPETITION ON VISITS TO COCOA ECOTOURISM DESTINATIONS - Suharijadi, Didik; Fausiyah, Diana; Astuti, Soekma Yeni (Seni Media Rekam ISI Surakarta, 2023)
The Banyuwangi Regional Government hosted a tourism vlog competition from 2017 to 2021. Because no analysis of the effectiveness of the competition has been conducted, additional research is required. The selection of cocoa tourist research objects in Sempu District is expected to become one of the community-based advertising references. This qualitative study collects data through interviews, focused group discussions, and documentation. The qualitative data analysis was carried out by combining data on the implementation of the Vlog Competition from the Tourism, Creative Economy and Culture Office of Banyuwangi Regency with data from FGD results with a sample of Banyuwangi film creators and data on cocoa tourism visits in Sempu District. The analysis results indicate that the Tourism Vlog Competition is ineffective in increasing the number of cocoa tourism visits in Sempu District.